The Application of Translation Shift of English Verb Phrase to Indonesian in Translation Teaching - Haryanti, Dwi; Prasetyarini, Aryati; Hikmat, Mauly Halwat; Sabardila, Atiqa; Laila, Malikatul; Haryanto, Sigit (Prosiding University Research Colloquium, 2023)
This article aims at classifying translation shifts of English verb phrase into Indonesian and describing the application of the translation shift in translation teaching. The data are in the forms phrases, clauses, and sentences containing verb phrases and their Indonesian transalation. The data were collected using content analysis, questionnaire, and interview. They were analyzed using Catford theory of translation shifts. The first result indicates that there are three translation shifts. They are structure shift, rank or level shift, and intra-system shift. Second finding shows that there are thirteen steps in translation teaching. Most procedures in teaching translation activated students as the approaches used were project-based learning and students centered learning. The process of teaching and learning by applying research results and doing directly as found in the examples makes it easier for students to understand the material provided.